Garden pea: agronomic, color and quality characterization using morphological and molecular data - Esposito, Maria Andrea; Bermejo, Carolina J.; Guindon, María Fernanda; Palacios Martínez, Laura Tatiana; Gatti, Ileana (Ediciones INTA, 2024)
During 2019 and 2020, 24 varieties of garden pea were sown under drip irrigation and dry-land conditions to evaluate the agronomic, grain color and quality traits. A molecular characterization was performed using SSR and SRAPS molecular markers. A high diversity at morphological and molecular levels was found among them. The variance components— genotypic (CVG), phenotypic (CVP) and environmental (CVE) coefficients of variation and heritability in the broad sense (H2)—were calculated. A CVG/CVP ratio close to or greater than one indicates that selection based on phenotype can result in gain (traits C, PLH, PL, DFH, L, a, b; HUE, CRO, CI, Ca and Cb), while a low or intermediate ratio indicates that phenotypic selection will not be effective. A Cluster analysis combining morphological and molecular data allowed the formation of five highly differentiated groups regarding expressed and underlying variability. Hybridization of members of the most distant Clusters may originate a segregating population with high variability to initiate a breeding program.